EKSTRAK KARAGINAN RUMPUT LAUT (Eucheuma cottonii) YANG DIPEROLEH DARI PANTAI TABLOLONG - Runa Matias Ruku; Alfred G.O Kase; Hartini R.L Solle (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
ABSTRACTEucheuma cottonii (E. cottonii) seaweed is a low level plant that has a high nutritional value. One of the ingredients that play a role in the formation of texture is carrageenan.Carrageenan is a type of hydrocolloid extracted from the seaweed of the red algae group (Rhodophyceae). The purpose of this study was to determine the quality of yields of Seaweed Carrageenan Extract (E. cottonii) obtained from Tablolong beach in the form of yield, ash content and fat content. The method used in this study is an experimental method with a completely randomized design (CRD) and for fat testing using quantitative descriptive methods. This study uses various concentrations of 0.1 N KOH, 0.2 N KOH, 0.3 N KOH and 0.4 N KOH. The results of the carrageenan yield test show that the addition of 0.1 N KOH concentration has a value of 56.10, KOH 0 , 2 N 62.16, KOH 0.3 N 72.73 and the best treatment was at P4 KOH 0.4 N 80.90. Carrageenan ash content test results showed that the addition of KOH concentration value obtained P1 KOH 0.1 N was 60.50, P2 KOH 0.2 N was 70.70, P3 KOH 0.3 N was 80.50, and P4 KOH 0.4 with a value of 90.50. The results of the carrageenan fat content of 0.1 KOH treatment has a fat content of 0, 2 while the treatment of KOH 0,2, KOH 0,3, KOH 0,4 have no fat content by showing the value (0). The results showed that the highest yield in the treatment of KOH concentration of 0.4 N with a value 80.95% and carrageenan ash content has the highest value in the treatment concentration of 0.4 N with a value of 90.50% while the fat content has a value of 0.2 in the treatment of KOH concentration of 0.1 N Keywords: Carrageenan, extract of E. cottonii seaweed.